2022
DOI: 10.1155/2022/8922021
|View full text |Cite
|
Sign up to set email alerts
|

Chondroprotective Effects of Gubitong Recipe via Inhibiting Excessive Mitophagy of Chondrocytes

Abstract: Objective. Osteoarthritis (OA) is the most common degenerative joint disorder and a leading cause of disability. A previous randomized controlled trial has shown that Gubitong (GBT) recipe can improve OA-related symptoms and articular function without noticeable side effects. However, the underlying mechanisms remain unclear. This study aims to explore the therapeutic mechanisms of the GBT recipe for OA through in vivo and in vitro experiments. Methods. Rats of the OA model were established by Hulth surgery an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Apart from TXC, a variety of herbal compound formulas have been used clinically for the treatment of OA in China, which may be associated with its chondroprotective effects through regulating autophagy of chondrocytes ( 58 ). The results of multicenter randomized controlled trials (RCT) showed that OA patients treated with shaoyang xibi decoction had lower Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score and less adverse events than those treated with meloxicam alone ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from TXC, a variety of herbal compound formulas have been used clinically for the treatment of OA in China, which may be associated with its chondroprotective effects through regulating autophagy of chondrocytes ( 58 ). The results of multicenter randomized controlled trials (RCT) showed that OA patients treated with shaoyang xibi decoction had lower Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score and less adverse events than those treated with meloxicam alone ( 59 ).…”
Section: Discussionmentioning
confidence: 99%